The luck of Pokey Bloom - Conford, Ellen (New York : Little Brown & Company, 1977)
A young girl learns that winning and getting along with people are often more than a matter of luck.
Booklist
Library Journal
School Library Journal
5.1
3-6.
3-6
Keywords: Behavior -- Fiction; Human behavior -- Fiction